The routine use of nasopharyngeal airway in the setting of monitored anesthesia care during gastrointestinal endoscopy: A multi-center single blinded randomized controlled trial - Christian Raphael; Nancy Abou Nafeh; Marc Moukarzel; Thuraya HajAli; Eliane Alhalabi; Aliyya Dabbous; Raji Naamani; Patrick Maroun; Yasser Sheib; Marie T. Aouad; Rony Al Nawwar (PLoS ONE, 2026)
Background and Aims Monitored anesthesia care (MAC) is commonly used for gastrointestinal (GI) endoscopy, allowing patients to breathe spontaneously while sedated. Despite its benefits, MAC is associated with respiratory adverse events, such as desaturation or the need for interventions. Limited studies have examined the effectiveness of nasopharyngeal airways (NPA) in reducing airway maneuvers and improving respiratory stability during MAC. The study evaluates the efficacy and safety of NPA in reducing the occurrence of at least one airway intervention/desaturation in patients undergoing GI endoscopy under MAC. Methods This multi-center, single-blinded randomized controlled trial involved patients undergoing GI endoscopy under MAC. A total of 329 patients were randomly assigned to either the NPA or control group. Primary outcomes included a composite primary outcome: occurrence of at least one airway intervention/desaturation. Secondary outcomes included adverse events, satisfaction scores of patients and healthcare providers, and the joint effects of NPA use and OSA risk on the occurrence of at least one airway intervention or desaturation. Results The NPA group showed significantly lower incidence of occurrence of at least one airway intervention/desaturation compared to controls (18.5% vs. 40.1%, P < 0.001). NPA significantly reduced the occurrence of at least one airway intervention/desaturation in both low and intermediate/high risk OSA groups. The reduction was stronger in low OSA risk group (OR=0.23, 95%CI [0.11–0.49]) versus intermediate/high OSA risk group (OR=0.45, 95%CI [0.21–0.95]. Health care provider satisfaction was significantly higher in the NPA group (p < 0.001). Mild, self-resolving epistaxis occurred in 3.1% of NPA patients. Conclusions NPA use reduces airway interventions and enhances satisfaction among anesthesiologists and gastroenterologists during GI endoscopy under MAC. Routine utilization of NPAs in this context may be considered.